Boma Technique Rescue of Orphaned Tiger Cubs by Using Ecological Factors - Raikwar, Hemant Kumar (Indian Forester, 2024)
Obedullahganj Forest division comprises of two sanctuaries with diversified flora and fauna. Remarkable increases in Tiger and leopard population of Ratapani sanctuary and adjacent forest could achieve by managing resource competition and related confrontations. Success story of safely capturing orphan tiger cubs of Ratapani sanctuary is based on ecological concept of utilization pattern of same resource and efforts to establish a correlation between resources sharing, behavioural adjustment and developed niche was made. Ratapani management utilised these ecological based concept i.e. temporal and spatial distribution, travel lane to capture tiger cubs. Boma chain link fence utilised for that. May be first time, Boma technique was utilised to rescue Tiger cubs or any carnivore.